Qualitative studies of silence : the unsaid as social action - Murray, Amy Jo; Durrheim, Kevin (Cambridge : Cambridge University Press, 2019)
Qualitative Studies of Silence brings together influential qualitative researchers from across the social sciences and humanities who have sought to understand the power of what remains unsaid, both psychologically and socially. Each chapter identifies one or more signs of silence and explains how these can form the basis of a rigorous qualitative investigation. The authors also demonstrate how silences operate in our private and collective lives by fulfilling psychological, relational, institutional, and ideological functions. The book contains multiple disciplinary perspectives and presents analyses of wide-ranging topics, such as medical consultations, whistleblowers, silence in court, omission-as-propaganda, trauma survivors, the silence of war museums, racism in the Americas, gendered silences, paid domestic labour, the undocumented student movement, and the Nazi past. This collection shows how such qualitative studies can reveal and contribute to understanding the unsaid as social action.
Introduction : A turn to silence / Amy Jo Murray, Kevin Durrheim -- Literal and metaphorical silences in rhetoric : examples from the celebration of the 1974 revolution in the Portuguese parliament / Michael Billig, Cristina Marinho -- Seeing silenced agendas in medical interaction : a conversation analytic case study / Merran Toerien, Clare Jackson -- Listening to the sound of silence : methodological reflections on studying the unsaid / Eviatar Zerubavel -- Social silences : conducting ethnographic research on racism in the Americas / Christina A. Sue, Mary Robertson -- Intimate silences and inequality : noticing the unsaid through layered data / Amy Jo Murray, Nicole Lambert -- Silence in the court : moral exclusion at the intersection of disability, race, sexuality, and methodology / Susan Opotow, Emese Ilyes, Michelle Fine -- Silencing self and other through autobiographical narratives / Robyn Fivush, Monisha Pasupathi -- Gendering the unsaid and the unsayable / Gregory Coles, Cheryl Glenn -- The language ideology of silence and silencing in public discourse : claims to silencing as metadiscursive moves in German anti-political correctness discourse / Melani Schroter -- Propaganda by omission : the case of topical silence / Tom Huckin -- Silencing whistleblowers / C. Fred Alford -- Between sound and silence : the inaudible and the unsayable in the history of the First World War / Jay Winter -- Affect and the unsaid : silences, impasses, and testimonies to trauma / Michael Richardson, Kyla Allison -- The unsaid and the unheard : acknowledgement, accountability, and recognition in the face of silence / Stephen Frosh -- Topographies of the said and unsaid / Kevin Durrheim, Amy Jo Murray
Title from publisher's bibliographic system (viewed on 28 Jun 2019).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Silence -- Social aspects; Silence -- Political aspects; Social sciences -- Methodology; Silence -- Aspect social; Silence -- Aspect politique; Social sciences -- Methodology; Electronic book